Pitch-specific advanced analytic and pitch-tracking risk factors for ulnar collateral ligament injuries in major league baseball pitchers - Mastroianni, M. A.; Kunes, J. A.; Mueller, J. D.; Obana, K. K.; Confino, J.; Luzzi, A. J.; Rondon, A. J.; Trofa, D. P.; Popkin, C. A.; Jobin, C. M.; Levine, W. N.; Ahmad, C. S. (The American Journal of Sports Medicine, 2025)
Background: The utilization of new pitch-tracking metrics has driven player development and provides more predictive pitch-specific data on physical characteristics and performance. Given the differences in each pitcher's arsenal, these pitch-specific metrics provide new potential variables to investigate ulnar collateral ligament (UCL) injury risk.